Cash Waqf Literacy and Religiusity on People’s Interest in Waqf Post Covid-19 in Banda Aceh City - Syafruddin Kamal; Hendra Syahputra; Mursalmina Mursalmina (Faculty of Islamic Business and Management, 2025)
This study critically evaluates the growing interest in cash waqf in Banda Aceh City during the post-COVID-19 era, with a specific focus on the influence of cash waqf literacy and religiosity. Distinguishing itself from prior research, this study rigorously examines 299 respondents through a simple random sampling method, ensuring broad representativeness. Data were processed using Structural Equation Modeling (SEM) and the Analysis of Moment Structures (AMOS) software, allowing for robust hypothesis testing. The results provide compelling evidence that both cash waqf literacy and religiosity are significant determinants of increased participation in cash waqf. This positive relationship underscores the urgent need for strategic initiatives by the Banda Aceh Municipal Government to intensify socialization efforts. Through partnerships with Sharia Financial Institutions Receiving Cash Waqf (LKS-PWU) and religious leaders, these efforts can substantially enhance public engagement and mobilize the latent potential of cash waqf. The findings not only reaffirm the critical role of literacy and religiosity in waqf participation but also emphasize the broader implications for economic resilience and community welfare in post-pandemic recovery. This study highlights the transformative potential of targeted policies to unlock the full capacity of cash waqf as a vital instrument for sustainable development.